STUDI FENOMENOLOGI TENTANG KESENJANGAN KETERAMPILAN DIGITAL DALAM PEMANFAATAN APLIKASI E-DUKCAPIL - Nayla Salsabila; Dewi Noor Azijah; Lolita Deby Mahendra Putri (LPPM Universitas Abdurrab, 2026)
affect the community’s ability to utilize the E-Dukcapil application in Cigunungsari Village, Tegalwaru District, Karawang Regency. The research focuses on the community’s psychomotor experiences in accessing and using online-based population administration services. A qualitative approach with a phenomenological method was employed, as this method allows researchers to explore the meanings of residents’ subjective experiences regarding the implementation of the digital system. Research data were collected through in-depth interviews, field observations, and documentation involving village officials and residents who had used the E-Dukcapil application. The findings indicate that most community members experience difficulties in understanding the application workflow, uploading documents, and following the established digital procedures. Low levels of digital literacy, limited assistance from village officials, and minimal socialization activities are the main factors contributing to the digital skills gap. These obstacles demonstrate that the success of digital transformation in public services depends not only on the availability of technology but also on the community’s ability to independently master and operate the system.